I just don't know what to do with the negative exponents.
how do you simplify this expression: 12x(9xy^12)(-5x^-8y^7)?
Remember the following rules when dealing with exponents.
am*an = am+n.
am/an = am-n.
a-n = 1/an.
Also remember that
a0 = 1.
Also it may help to remember that you can regroup the terms according to bases.
To illustrate I'll use another example, and leave yours for you to try.
2*x(9*x*y3)(3*x-2y4) = (2*9*3)(x*x*x-2)(y3*y4).
I hope that helps some.
Try a bit of this, and if you still need help, I or another tutor here will be happy to assist you.